Explaining cross-racial differences in the educational gender gap - Aucejo, Esteban (2013)
The sizable gender gap in college enrolment, especially among African Americans, constitutes a puzzling empirical regularity that may have serious consequences on marriage markets, male labor force participation and the diversity of college campuses. For instance, only 35.7 percent of all African American undergraduate students were men in 2004. Reduced form results show that, while family background covariates cannot account for the observed gap, proxy measures for non-cognitive skills are crucial to explain it. Moreover, a sequential model of educational attainment indicates that males have actually higher preferences for education than females after controlling for latent factors (i.e. cognitive and non-cognitive skills). The model also shows that cognitive skills strongly affect the decision to move from one school level to the next, especially after finishing high school, but cannot account for disparities between genders. On the contrary, the substantial differences in the distribution of non-cognitive skills between males and females make these abilities critical to explain the gender gap in educational attainment across and within races